according to your solutions, the equation would factor to
(3x-1)(x-3) = 0
would this give you the original equation?
Clearly not!
so , like I asked before, how are you getting your answers?
What method are you using?
solve for x
3x^2-12x+3=0
is the answer 1/3, 3
3 answers
I tried it your way and this is what I came up with
x = 2�} 6�ã3
am I right?
x = 2�} 6�ã3
am I right?
use the formula
x = (-b ±√(b^2-4ac)/(2a)
= (12 ± √108)/6
= (12 ±6√3)/6
= 2 ± √3
x = (-b ±√(b^2-4ac)/(2a)
= (12 ± √108)/6
= (12 ±6√3)/6
= 2 ± √3